Localized incorporation of outer membrane components in the pathogen Brucella abortus - Vassen, Victoria (John Wiley and Sons Inc., 2019)

(untitled) (EMBO J)
The zoonotic pathogen Brucella abortus is part of the Rhizobiales, which are alpha‐proteobacteria displaying unipolar growth. Here, we show that this bacterium exhibits heterogeneity in its outer membrane composition, with clusters of rough lipopolysaccharide co‐localizing with the essential outer membrane porin Omp2b, which is proposed to allow facilitated diffusion of solutes through the porin. We also show that the major outer membrane protein Omp25 and peptidoglycan are incorporated at the new pole and the division site, the expected growth sites. Interestingly, lipopolysaccharide is also inserted at the same growth sites. The absence of long‐range diffusion of main components of the outer membrane could explain the apparent immobility of the Omp2b clusters, as well as unipolar and mid‐cell localizations of newly incorporated outer membrane proteins and lipopolysaccharide. Unipolar growth and limited mobility of surface structures also suggest that new surface variants could arise in a few generations without the need of diluting pre‐existing surface antigens.